A distinct clinicopathological variant of focal cortical dysplasia IIId characterized by loss of layer 4 in the occipital lobe in 12 children with remote hypoxic–ischemic injury. (23rd August 2017) - Wang, Dan‐Dan; Piao, Yue‐Shan; Blumcke, Ingmar; Coras, Roland; Zhou, Wen‐Jing; Gui, Qiu‐Ping; Liu, Cui‐Cui; Hu, Jing‐Xia; Cao, Li‐Zhen; Zhang, Guo‐Jun; Lu, De‐Hong
Summary: Objective: In 2011, the International League Against Epilepsy (ILAE) proposed a consensus classification system of focal cortical dysplasia (FCD) to distinguish clinicopathological subtypes, for example, "isolated" FCD type Ia–c and IIa–b, versus "associated" FCD type IIIa–d. The histopathological differentiation of FCD type I and III variants remains, however, a challenging issue in everyday practice. We present a unique histopathological pattern in patients with difficult‐to‐diagnose FCD, which highlights this dilemma, but also helps to refine the current ILAE classification scheme of FCD. Methods: We present a retrospective series of 11 male and one female patient with early onset pharmacoresistant epilepsy of the posterior quadrant (mean age at seizure onset = 4.6 years). All surgical specimens were reviewed. Clinical histories were retrieved and extracted from archival patient files. Results: Microscopic inspection revealed abnormalities in cortical architecture with complete loss of layer 4 in all surgical samples of the occipital lobe, as confirmed by semiquantitative measurements (p < 0.01). Clinical history reported early transient hypoxic condition in nine patients (75%). Magnetic resonance imaging (MRI) revealed abnormal signals in the occipital lobe in all patients, and signal changes suggestive of subcortical encephalomalacia were found in seven patients. Surgical treatment achieved favorable seizure control (Engel class I and II) in seven patients with an available follow‐up period of 6.1 years. Significance: Prominent disorganization of cortical layering and lack of any other microscopically visible principle lesion in the surgical specimen would result in this neuropathological pattern hitherto being classified as FCD ILAE type Ib. However, perinatal hypoxia with distinctive MRI changes suggested primarily a hypoxemic lesion and acquired pathomechanism of neuronal cell loss in the occipital lobe of our patient series. We propose, therefore, classifying this distinctive clinicopathological pattern as a separate variant of FCD ILAE type IIId.